Losing ground at the wrong time: trends in self-reported influenza vaccination uptake in Switzerland, Swiss Health Survey 2007–2017. Issue 2 (9th February 2021) - Zürcher, Kathrin; Zwahlen, Marcel; Berlin, Claudia; Egger, Matthias; Fenner, Lukas
Abstract : Objectives: We studied time trends in seasonal influenza vaccination and associations with socioeconomic and health-related determinants in Switzerland, overall and in people aged ≥65 years. Design: Three cross-sectional surveys. Participants: Individuals who participated in the Swiss Health Surveys 2007, 2012 and 2017. We calculated the proportion reporting influenza vaccination in the last 12 months, and performed multivariable logistic regression analyses. Results: We included 51 582 individuals in this analysis. The median age was 49 years (IQR 25–64), and 27 518 were women (53.3%). The proportion of reporting a history of influenza vaccination overall was 31.9% (95% CI 31.4 to 32.4); and dropped from 34.5% in 2007 to 28.8% in 2017. The uptake of vaccination within the past 12 months was 16% in 2007 and similar in 2012 and 2017 (around 14%). In people with chronic disease, uptake dropped from 43.8% in 2007 to 37.1% in 2012 and to 31.6% in 2017 (p<0.001). In people aged ≥65 years, uptake dropped from 47.8% in 2007 to 38.5% in 2012 to 36.2% in 2017 (p<0.001). In logistic regression, self-reported vaccination coverage decreased in the 65–75 years old (adjusted OR (aOR) 0.56, 95% CI 0.48 to 0.66 between 2007 and 2012; aOR 0.89, 95% CI 0.77 to 1.03 between 2012 and 2017). Uptake was positively associated with the ≥65 age group, living in French-speaking and urban areas, history of smoking, bad self-reported health status, private/semiprivate health insurance, having a medical profession and having any underlying chronic disease. Conclusion: Influenza vaccination coverage was low in older and chronically ill persons. Significant efforts are required in preparing for the influenza season 2020/2021 to reduce the double burden of COVID-19 and seasonal influenza. These efforts should include campaigns but also novel approaches using social media.